The Sale of Prescription Medicines Through E-Commerce Platform Without Prescription: Between Urgency And Compliance - Shalmont, Jerry; Darmawan, Grace Iskandar; Dominica, Dora (Universitas Brawijaya, 2024)
The sale of prescription medicines through e-commerce platforms is allowed by attaching the original medical prescription (electronic or handwritten prescriptions) and uploading it to the platforms. However, some parties sold it without the prescription, and some consumers still purchased those medicines. This research is focused on the cause of high demand in terms of the sale and purchase of prescription medicines without medical prescriptions on e-commerce platforms, as well as relevant solutions. This research is normative – empirical legal research, using regulatory and conceptual approaches. Based on the questionnaire and interview results, the consumers purchased those medicines through e-commerce platforms without prescription due to urgent needs. The analysis shows that a lack of consumer awareness of their rights is the main culprit of this phenomenon. In short, consumer awareness needs to be improved regarding compliance with the relevant laws and regulations for safety reasons.